Nilai-Nilai Hadis Nabi Pada Manajemen Evaluasi Dalam Meningkatkan Profesionalisme Guru di Sekolah Dasar Islam Ruhama Kota Bogor - Ihya, Syahidul; Rohaemi; Aspandi; Machdum Bachtiar (Universitas Islam Tribakti Lirboyo Kediri, 2024)
In the process of Islamic education management, the role of the principal becomes a benchmark in the success of an educational institution. This form is realized by the head of the Ruhama Tahfidzul Qur'an Islamic Elementary School in carrying out school management evaluation activities based on the values of the Prophet's hadith. These activities are able to improve teacher professionalism. However, this has not been realized by all three centers of education, so it becomes an important thing to research. Therefore, the objectives of this study are (1) to describe the form of evaluation management activities at Ruhama Islamic Elementary School Thfidzul Qur'an Bogor City (2) to analyze the actualization of hadith values in school evaluation management in improving teacher professionalism at Ruhama Islamic Elementary School Bogor City. This type of research is a case study field research at the institution of Ruhama Islamic Elementary School Tahfidzul Qur'an Bogor City. This research uses a qualitative approach, namely analyzing the values of the prophet's hadith actualized by the principal in management evaluation activities at Ruhama Islamic Elementary School in Bogor City. Data sources were obtained through observations and interviews with several research subjects including principals, teachers and all related stakeholders. The research used the hadith perspective to analyze the values of the Prophet's hadith actualized by the principal in school management evaluation activities in improving teacher professionalism at Ruhama Tahfiddzul Qur'an Islamic Elementary School in Bogor City. The results of the study show that the values of the Prophet's hadith in the evaluation management carried out by the principal have been actualized properly, these activities include: Academic evaluation, administrative evaluation, evaluation of student achievement and supervision of the school committee.